Safe, or not safe? Covered bonds and Bank Fragility - Toni Ahnert; Kartik Anand; Prasanna Gai; James Chapman (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We explore the relationship between asset encumbrance and bank funding in the context of covered bonds a form of collateralized debt. Covered bond issuance influences the incidence of bank runs by unsecured creditors and, in turn, conditions in the unsecured funding market influence the bank s choice of asset encumbrance. The more reliant is the bank on secured finance and the more it encumbers assets on its balance sheet, the more concentrated are losses on unsecured creditors and the more fragile the bank. But as more stable long-term debt is added to the funding mix, the greater is the expected value of bank equity. We solve for the optimal choice of asset encumbrance and wholesale funding. Our model sheds light on how losses of confidence in funding markets, macroeconomic shocks, and improved crisis resolution frameworks affect the extent of balance sheet collateralization.
Keywords: G01; G21; D82; 330